Kinetic Studies on Thermal Decomposition of Mixed Ligand Complexes of Lanthanide(III) Ions - RAJENDRAN , G.; USHA DEVI, K.G. (Asian Journal of Chemistry, 2010)
Some mixed ligand complexes of lanthanide(III) ions with 4-hydroxy-3',4-dimethoxy diphenyl azomethine (HDDA) and diphenyl sulfoxide (DPSO) and various coordinating anions such as nitrate, perchlorate and thiocyanate have been synthesized and their kinetics on thermal decomposition were studied. The activation energies for the decomposition stages were calculated by Coats-Redfern and Madhusoodhanan-Krishan-Ninan equations. The tentative mechanism for the thermal decomposition has been proposed.